Stranger magic : charmed states & the Arabian nights - Warner, Marina, 1946- (London : Vintage, 2012)
Our foremost theorist of myth, fairytale, and folktale explores the magical realm of the imagination where carpets fly and genies grant prophetic wishes. Stranger Magic examines the profound impact of the Arabian Nights on the West, the progressive exoticization of magic, and the growing acceptance of myth and magic in contemporary experience
Winner of Sheikh Zayed Book Awards 2013.
Includes bibliographical references (pages [499]-516) and index.
Originally published: London : Chatto and Windus, 2011
Keywords: Arabian nights; Arabian nights -- Influence; Arabian nights -- Appreciation -- Europe; Arabian nights -- Translations; Myth in literature; Orientalism in literarue; Tales -- Arabian Peninsula -- History and criticism; Magic in literature; Tales -- Arabian Peninsula